An Islamic Law Review of the Practice of Selling Confiscated Items at Pondok Pesantren Riyadhul Amien Danau Lamo - Silvina Dwi Ruswadi; Nilfatri; Reza Okva Marwendi; Alisyah Pitri (Zabags International Journal of Islamic Studies, 2025)
This study examines the practice of confiscating and subsequently selling abandoned personal items at Pondok Pesantren Riyadhul Amien Danau Lamo from the perspective of Islamic law, focusing on the legitimacy of ownership transfer and conformity with muamalah principles. The research responds to an institutional practice in which items left unattended by santri are collected by cleanliness officers, announced, cleaned, and later sold to support the pesantren’s cleaning needs. Employing a qualitative case study approach, data were gathered through direct observation, in-depth interviews with administrators and students, and review of internal documentation, then analyzed via data reduction, thematic presentation, and verification. Findings indicate that confiscation and resale are conducted openly, including prior announcement, and that proceeds are allocated to communal cleaning supplies rather than private gain. From an Islamic legal standpoint, the practice may be considered permissible provided it meets the criteria of transparency, adequate announcement, and utilization for the common good (maslahah). The study contributes to extending the application of the concept of al-milkiyyah (ownership) beyond state and financial contexts into Islamic educational institutions, and offers a basis for pesantren to develop written, accountable, and sharia-compliant regulations regarding confiscated property